Are profiles of social, cultural, and economic capital related to living well with dementia? Longitudinal findings from the IDEAL programme. (January 2023) - Sabatini, Serena; Martyr, Anthony; Gamble, Laura D.; Jones, Ian R.; Collins, Rachel; Matthews, Fiona E.; Knapp, Martin; Thom, Jeanette M.; Henderson, Catherine; Victor, Christina; Pentecost, Claire; Clare, Linda; et al.
Abstract: Rationale: Research exploring social, cultural, and economic capital among people with dementia is scarce. Objective: We describe levels of social, cultural, and economic capital in people with dementia at baseline and levels of social and cultural capital 12 and 24 months later. We identify groups of people with dementia having different combinations of capital and explore whether the identified groups differ in personal characteristics at baseline and in quality of life (QoL), satisfaction with life (SwL), and well-being over time. Method: Baseline, 12-months, and 24-months data from 1537 people with dementia (age, mean = 76.4 years; SD = 8.5; Alzheimer's Disease = 55.4%) enrolled in the IDEAL cohort were analyzed. Social (interactions with friends, civic participation, social participation, neighborhood trust, social network), cultural (education, cultural participation) and economic (annual income) capital, QoL, SwL, well-being, and personal characteristics were assessed. Results: Compared to people their age, people with dementia reported slightly lower frequency of interactions with friends, social networks and social support, civic and cultural participation, education, and annual income. However, social engagement, cultural participation, and annual income are low among British older adults. Latent profile analysis identified four groups that, based on their levels of social, cultural, and economic capital were named socially and economically privileged (18.0% of participants); financially secure (21.0% of participants); low capital (36.9% of participants); and very low capital (24.1% of participants). Latent growth curve models showed that over time QoL, SwL, and well-being remained largely stable for all groups. Compared to the low capital group, the socially and economically privileged and financially secure groups had higher QoL and well-being whereas the group with very low capital had poorer QoL, SwL, and well-being. Conclusions: New policies and efforts from the government, philanthropic foundations, the voluntary and primary care sectors are needed to address social, cultural, and economic disadvantage among people with dementia. Highlights: Social and cultural participation are low among British people with dementia. Compared to their peers 30% of people with dementia had equivalent or higher income. Social and cultural participation vary greatly among people with dementia. Those with better social capital had higher quality of life and well-being. Those with higher income had greater quality of life and well-being.